Central diabetes insipidus in children: Diagnosis and management. Issue 5 (September 2020) - Patti, Giuseppa; Ibba, Anastasia; Morana, Giovanni; Napoli, Flavia; Fava, Daniela; di Iorgi, Natascia; Maghnie, Mohamad
Abstract : Central diabetes insipidus (CDI) is a complex disorder in which large volumes of dilute urine are excreted due to arginine-vasopressin deficiency, and it is caused by a variety of conditions (genetic, congenital, inflammatory, neoplastic, traumatic) that arise mainly from the hypothalamus. The differential diagnosis between diseases presenting with polyuria and polydipsia is challenging and requires a detailed medical history, physical examination, biochemical approach, imaging studies and, in some cases, histological confirmation. Magnetic resonance imaging is the gold standard method for evaluating the sellar-suprasellar region in CDI. Pituitary stalk size at presentation is variable and can change over time, depending on the underlying condition, and other brain areas or other organs – in specific diseases – may become involved during follow up. An early diagnosis and treatment are preferable in order to avoid central nervous system damage and the risk of dissemination of germ cell tumor, or progression of Langerhans Cell Histiocytosis, and in order to start treatment of additional pituitary defects without further delay. This review focuses on current diagnostic work-up and on the role of neuroimaging in the differential diagnosis of CDI in children and adolescents. It provides an update on the best approach for diagnosis – including novel biochemical markers such as copeptin – treatment and follow up of children and adolescents with CDI; it also describes the best approach to challenging situations such as post-surgical patients, adipsic patients, patients undergoing chemotherapy and/or in critical care.